The Impact of Communication And Work Discipline on Performance: ( Studi Karyawan Pada Klinik Rawat Inap Ellisa Malang ) - Almer Rasyid; Muhammad Rizky Firdaus; Muhammad Alif Alfarizi (Lembaga Pengembangan Kinerja Dosen, 2024)
Human Resources is able to produce quality performance in a firm. To generate a high quality HR performance demands effective skill management, the variables that might affect the quality of HR performance are communication and work discipline that run simultaneously. The goal of this study is to determine and analyze the influence of communication and work discipline on employee performance, as well as to determine and analyze which of the two variables is the most dominating on the performance of Elisa Malang inpatient clinic staff. This topic has 47 respondents, employing sample collection technique is saturated sample research. Data collecting approaches using a questionnaire and Interviews. Data analysis with IBM SPSS Statistics. The results of this study can be stated that the factors of communication and work discipline have a simultaneous effect on the performance variable. The two communication factors have a significant but not significant effect on performance, while the work discipline variable has a significant effect. performance. And the results of the study also suggest that one of the variables has a more significant influence, namely the work discipline variable